2016
DOI: 10.1097/igc.0000000000000856
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Survival Benefits of Combined Chemotherapy and Radiotherapy Versus Chemotherapy Alone for Uterine Serous Carcinoma: A Meta-analysis

Abstract: ObjectiveTo date, there is no convincing evidence comparing the impact of combined chemotherapy and radiotherapy with chemotherapy alone in postoperative uterine serous carcinoma (USC), which remains an unclear issue. We conducted a meta-analysis assessing the impact of combined chemotherapy and radiotherapy compared to chemotherapy alone on overall survival in postoperative USC.MethodsA comprehensive search was performed in the databases of EMBASE, PubMed, Web of Science, and Cochrane Library from inception t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…Additionally, a meta-analysis comparing the effect of CT alone verses combined CT and RT on OS in women with USC showed that combined CT and RT reduced the risk of death compared with CT alone, and further analysis found a benefit for combined therapy for both early stage and advanced disease. 20 Similarly, 2 retrospective studies of women with USC found a survival benefit for combined therapy with CT and RT for patients with advanced-stage disease 19 and for women with all stages of USC. 25 Limited prospective evidence supports this approach, as a phase II trial of “sandwich” adjuvant pelvic RT and paclitaxel/carboplatin CT for patients with USC showed that this treatment is safe and efficacious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a meta-analysis comparing the effect of CT alone verses combined CT and RT on OS in women with USC showed that combined CT and RT reduced the risk of death compared with CT alone, and further analysis found a benefit for combined therapy for both early stage and advanced disease. 20 Similarly, 2 retrospective studies of women with USC found a survival benefit for combined therapy with CT and RT for patients with advanced-stage disease 19 and for women with all stages of USC. 25 Limited prospective evidence supports this approach, as a phase II trial of “sandwich” adjuvant pelvic RT and paclitaxel/carboplatin CT for patients with USC showed that this treatment is safe and efficacious.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Evidence regarding the role of RT in this disease is conflicting, with some studies failing to show a benefit whereas others have demonstrated improved outcomes with the addition of RT. 9 , 14 , 16 , 17 , 18 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…While a recent study showed that adjuvant chemotherapy (chemo) with or without radiotherapy (RT) is associated with improved survival [ 18 ], several studies show that both chemo and RT are associated with improved survival outcomes compared to adjuvant chemo alone or RT alone in women with USC [ 19 - 21 ]. A large meta-analysis suggested a survival benefit to combined chemo and RT (CRT) for patients with early USC [ 22 ]. All of these adjuvant strategies, including observation, are valid approaches for early-stage USC according to the most recent National Comprehensive Cancer Network Uterine Neoplasms guidelines (version 1.2021).…”
Section: Introductionmentioning
confidence: 99%
“…La prise en charge adjuvante des carcinomes séreux et à cellules claires comprend une chimiothérapie, une radiothérapie externe pelvienne suivies d’une curiethérapie. Une curiethérapie vaginale seule ou en association à une chimiothérapie peut être réalisée pour les stades IA sans emboles vasculaires complètement stadifiés [8] , [9] , [10] , [11] , [12] . La prise en charge adjuvante des carcinosarcomes et des carcinomes indifférenciés comprend une chimiothérapie systémique suivie d’une radiothérapie externe pelvienne et d’une curiethérapie [13] , [14] , [15] .…”
Section: Introductionunclassified